Response of calcified and non-calcified southern California seaweeds to increased CO₂ and temperature - Kram, Susan Laurel (eScholarship, University of California, 2013)
Anthropogenic carbon dioxide levels have increased rapidly in the last 300 years, leading to climate change phenomenons such as global warming and ocean acidification. Declining oceanic pH associated with ocean acidification is expected to negatively affect growth of calcified algae, but it is unclear how these conditions will impact non-calcifying algae. Likewise the combined effects of ocean acidification and global warming on seaweeds are largely unknown. CO₂ enrichment and warming experiments were conducted with seven species of southern California calcifying and non-calcifying seaweeds; algal growth, chlorophyll fluorescence, carbonic anhydrase activity, pigment concentration and photosynthetic oxygen production relative to irradiance were measured. Ambient seawater conditions were compared to treatment conditions where pH was reduced by 0.2 ± 0.05 units via a constantly bubbling a CO₂-air blend in continuous flow aquaria and/or temperature was increased 2°C ± 0.5°C. CO₂ enrichment significantly increased the growth rate of one fleshy alga while the others were not affected. Under high CO₂, one calcified alga had significantly decreased growth rates while the other two trended towards slower growth. A non- calcified alga experienced a significant negative interaction between the increased CO₂ and temperature treatment, but the calcified alga did not. Elevated CO₂ and/or temperature did not have a significant effect on pigment (chlorophyll a, and b, carotenoids and phycobilins) concentration, chlorophyll fluorescence, carbonic anhydrase activity or photosynthetic oxygen production for any of the species. These results suggest that calcified algae may be less competitive under more acidic oceanic conditions but inter-specific responses among non-calcified algae may vary